Maktabat al-Ḍāmirī wa-Dawruhā fī Nashr al-Fikr al-ʻUmānī wa-Turāthihi - Būḥajjām, Muḥammad ibn Qāsim Nāṣir (al-Muʼtamar al-Duwalī al-Khāmis bi-Mālīziyā: Ḥarakat al-Ṭibāʻah al-ʻUmānīyah wa-Atharuhā fī al-Tawāṣul al-Ḥaḍārī, 2018)
Maktabat al-Ḍāmirī for Publishing and Distribution was founded, in origin, to publish Ibāḍī thought and its heritage, given the richness of both and their civilizational role reaching far back, and given the importance of that heritage in the present and its dimensions for the future. It proceeded from the premise that this thought and this heritage are not known in the measure they possess in strength, effectiveness and effects within the global intellectual and civilizational movement — indeed they are at times subject to distortion, alteration, falsification and belittlement. The great role this publishing house has played, and continues to play, prompted the writing of this paper: to introduce it and its efforts, to present its strategy and working principles, its participation in exhibitions inside and outside the Sultanate, together with a survey of its publications, the subjects in which it has been distinguished, and its part in the civilizational contact between Oman and the Islamic Maghreb.
MHF-PRINT2018-022
Keywords: Maktabat al-Ḍāmirī; Publishing house; Ibāḍī thought; Omani heritage; Book distribution; Maghreb